Anti-media populism: Expressions of media distrust by right-wing media in India. Issue 2 (2nd April 2020) - Bhat, Prashanth; Chadha, Kalyani
ABSTRACT: Criticism of mainstream media as being "biased" has emerged as a defining characteristic of right-wing discourse all over the world. Such expressions are coupled with the establishment of right-wing news outlets that seek to undermine professional journalism. But while scholars have examined the operation of such outlets in the context of Western democracies, anti-media populism in the Global South has received little scholarly attention. Through a thematic analysis of articles published on OpIndia.com - a right-wing news site in India, this paper seeks to address this gap in the literature and identify the discursive strategies employed by the right-wing media to discredit the mainstream press in India.